Does feeling what you eat change how you eat? Implications of an intervention to promote consciousness of eating experiences - Palazzo, Carina Carlucci; Leghi, Barbara Esteves; Diez-Garcia, Rosa Wanda (Frontiers in Psychology, 2024)
This work aims to understand the experience of participating in the Food and Nutrition Education Program workshops with Sensory and Cognitive Exercises (PESC)and measure its impact on eating behavior. The PESC consists of four workshops with exercises stimulating perception and reflection on bodily sensations triggered in eating situations. It was developed to promote consciousness of eating experiences in women who reported difficulty in controlling their body weight and who increased over 5% of their body weight in the previous year. This is a mixed-methods study designed as a controlled trial. The intervention group (n = 19) was evaluated before the first workshop (T0) and after the last workshop (T1) and the control group (n = 18), which did not participate in the workshops, was evaluated twice (T0 and T1), with an interval of 3 to 4 weeks. At T0 and T1, it was applied the Intuitive Eating Scale (IES-2) and the Three Factor Eating Questionnaire (TFEQ-R21). In T1, the intervention group also participated in a qualitative interview. The interviews' analysis revealed the participants' selfobservation process, which led to the perception of their practices, priorities, intentions, eating difficulties, and the connection between these aspects and environmental issues.The following themes were considered: Food management/control, Body dissatisfaction, Reflection/re-signification, and Different ways of being in familiar contexts. After participating in the PESC, the intervention group showed an increase in the IES-2 total score (95% Confidence Interval = (0.10; 0.39)) and a decrease in the emotional eating scale score (95% Confidence Interval = (-16.03; -3.85)). The results allow us to infer that, after participating in the PESC, the intention to manage food intake became more effective, less susceptible to oscillations imposed by the external environment, and more supported by internal resources.